Instructional Edutainment Media "Number Game" Based on Mobile Technology to Improve Mathematical Conceptual Understanding - Laswadi, Laswadi; Rhomiy Handican; Eline Yanty Putri Nasution (Jurnal Edutech Undiksha, 2023)
Integrating technology into learning is a challenge for education in the current digital era, so innovation is needed to make students’ cognitive, constructive processes more optimal. This development research aims to produce edutainment media in the form of quality mobile technology-based "Number Game" video games. This type of research is developed using the ADDIE model. Methods of data collection using questionnaires and tests. The mobile game was implemented for VII graders of junior high school consisting of 34 students. The research instruments comprised media and material validation sheets, teacher and student practicality questionnaires, and conceptual understanding ability test instruments. The results showed that the "Number Game" edutainment media developed was valid with an average media validation score of 4.49, with a very good classification. The mean material validation score is 4.17, with a good classification. The "Number Game" game developed is practical, with an average teacher response questionnaire score of 3.75 with a good classification, an average student response questionnaire score is 3.35 with a good classification, and an average percentage of learning implementation is 93.51% with a very good category. The "Number Game" game effectively understood students’ concepts, with a learning completeness percentage of 67.64 with an effective classification. It is concluded that educational games are feasible and effective in learning.